2004
DOI: 10.1086/383048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Etiology of Bacteremia in Febrile Neutropenic Patients and the Susceptibilities of the Currently Isolated Pathogens

Abstract: The etiology of bacteremia in febrile neutropenic patients in the past few decades has shifted from gram-negative to gram-positive organisms. Potential reasons include the use of indwelling catheters, local environmental conditions, and the administration of specific antibiotic agents, especially as prophylaxis. Other factors may emerge from new studies, such as the categorization of febrile neutropenic patients into groups at low risk and at high risk of developing serious complications, continuing changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
0
26

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(181 citation statements)
references
References 42 publications
13
142
0
26
Order By: Relevance
“…The main change reported has been the reduction in the occurrence of bacteremia due to gram-negative organisms, with a shift to gram-positive organisms [4,5]. The causes of this change in the epidemiology of the infection have not been clearly identified, but they may include more aggressive radiotherapy and chemotherapy, more profound and prolonged neutropenia, increased use of intravenous catheters, and selective pressure of antibiotics [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main change reported has been the reduction in the occurrence of bacteremia due to gram-negative organisms, with a shift to gram-positive organisms [4,5]. The causes of this change in the epidemiology of the infection have not been clearly identified, but they may include more aggressive radiotherapy and chemotherapy, more profound and prolonged neutropenia, increased use of intravenous catheters, and selective pressure of antibiotics [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The causes of this change in the epidemiology of the infection have not been clearly identified, but they may include more aggressive radiotherapy and chemotherapy, more profound and prolonged neutropenia, increased use of intravenous catheters, and selective pressure of antibiotics [4,5]. It was previously reported that identification of the causative microorganisms of infection is possible in only 22-39% of cases [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the factors implicated in the increasing number of Gram-positive bacteraemias were the administration of aggressive chemotherapy and radiotherapy regimens that induced severe mucositis, increased use of indwelling catheters, the widespread use of fluoroquinolones as prophylactic agents, and empirical antibiotic treatment with high activity against Gram-negative infections [25][26][27]. Yet, this shift towards Gram-positive bacteraemias has not been global.…”
Section: Bacteraemiamentioning
confidence: 99%
“…Se considera que un paciente tiene neutropenia cuando la cifra absoluta de neutrófilos es menor de 1.000/mm 3 . El riesgo de infección aumenta con la severidad de la neutropenia, duración de ésta, control de la neoplasia, intensidad del tratamiento quimioterápico, daño en las barreras naturales (piel, mucosas), empleo de catéteres tunelizados, realización de procedimientos invasivos, enfermedad dental, empleo de profilaxis antifúngica y alteraciones coexistentes de la inmunidad celular o humoral.…”
Section: Profilaxis Antibacteriana En El Paciente Neutropénicounclassified